Корпоративная социальная ответственность как основной нематериальный актив компании ХХІ века - Касабова, І. А. (Ways to Improve Construction Efficiency, 2012)
The CSR and its implementation in company vital issues are researched. CSR is analyzed as a basic intangible asset in company of the 21st century.